2000
DOI: 10.1007/bf03401830
|View full text |Cite
|
Sign up to set email alerts
|

Interferons and IRF-1 Induce Expression of the Survival Motor Neuron (SMN) Genes

Abstract: We identified a candidate Interferon-Stimulated Response Element (ISRE), overlapping with an Interferon Regulatory Factors binding motif (IRF-E) in the promoter region of SMN and SMNc genes. Both ISRE and IRF-E motifs are involved in mediating transcriptional induction of interferon-stimulated gene expression. We, therefore, investigated whether SMN and SMNc genes were regulated by interferons (IFN). Here we show that both IFN-beta and IFN-gamma rapidly induced SMN and SMNc mRNA and protein expression in vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 30 publications
0
23
0
2
Order By: Relevance
“…In the present study, compounds such as forskolin and dibutyryl cAMP were shown to increase the expression of the SMN2 gene. Interferon ␤ and ␥ have been shown to bind to an ISRE element in the SMN promoter and activate SMN expression (31). In some cases, the activation results in a greater increase in the exon⌬7SMN isoform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, compounds such as forskolin and dibutyryl cAMP were shown to increase the expression of the SMN2 gene. Interferon ␤ and ␥ have been shown to bind to an ISRE element in the SMN promoter and activate SMN expression (31). In some cases, the activation results in a greater increase in the exon⌬7SMN isoform.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of SMN2 in all SMA patients, the ability of more copies of SMN2 to modify the SMA phenotype, and the rescue of SMA mice by multiple copies of SMN2 make it an attractive therapeutic candidate. Molecules capable of inducing SMN2 expression (30,31) or altering the splicing of SMN2 such that more full-length SMN transcript is produced have been identified (32)(33)(34)(35)(36)(37). At the present time, there is limited information on the mode of action of these compounds as well as the protein complexes that interact with the SMN promoter.…”
mentioning
confidence: 99%
“…Interferon-stimulated gene expression inducing SMN mRNA has been reported. 15 Moreover, aclarubicin, a tetracyclin derivative, has been shown to increase fl SMN production by modifying the isoform ratio. 16 However, the side effects of interferon treatment and the toxicity of aclarubicin advice against the use of these drugs for therapy of young SMA patients.…”
Section: Introductionmentioning
confidence: 99%
“…The consequence of differential transcription start site usage remains unclear. A small number of transcription factors regulating the core SMN promoter have been identified including IFNg and IFNb [Baron-Delage et al, 2000], the CRE binding protein CREB-1 [Majumder et al, 2004] as well Sp and Ets family members [Rouget et al, 2005]. Finally, core SMN promoter activity can be modulated by a number of upstream enhancer and silencer elements [Echaniz-Laguna et al, 1999;Monani et al, 1999;Boda et al, 2004]; however, aside from their location, little else is known about their function.…”
Section: Are Smn1 and Smn2 As Identical As They Appear To Be?mentioning
confidence: 99%